Effect of binder and silica sand on unconfined compressive strength of cemented peat - Sing W.L.; Hashim R.; Ali F. (2023)
The aim of this paper is to evaluate the unconfined compressive strength of cemented peat in comparison to that of untreated peat. A laboratory study on the unconfined compressive strength of cemented peat is important in order to formulate a suitable and economical mix design for stabilized peat columns developed in deep peatland to support highway construction. To characterize the strength behavior of cemented peat, 14 test specimens of different mix designs of the cemented soil were prepared and tested in unconfined compression tests. The results revealed that test specimen with a mix design of 300 kg m-3 binder dosage by mass of wet peat (90% MASCRETE and 10% kaolinite in composition), 4% calcium chloride by mass of binder, and 25% silica sand by volume of wet peat gave the highest unconfined compressive strength of 413.0 kPa after 7 curing days in water. Such positive finding was largely attributed to the reactivity of the binder, calcium chloride and silica sand with wet peat. Thus, it can be concluded that high strength cemented peat can be produced when the MASCRETE and kaolinite stabilized peat admixture with silica sand acting as a filler, was activated by calcium chloride that accelerated the rate of cement hydration in the soil. 2011 Academic Journals.